EARLY VERSUS DELAYED ORAL INTAKE IN PATIENTS AFTER CESAREAN SECTION UNDER REGIONAL ANESTHESIA: Early Versus Delayed Oral Intake - Hassan, Laiqa; Tufail, Shazia; Aslam, Farheen; Mustafa, Nilofar; Ahmed, Arub; Qamar, Saima (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the outcome in early versus delayed oral intake in patients after cesarean section under regional anesthesia.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital Lahore, from Dec 2017 to May 2018.Methodology: A total of 352 women undergoing elective cesarean section under regional anesthesia, nil by mouth for at least 8 hours before surgery were divided in 2 groups. In group 1, patients were given sips of clear oral fluid (water)